Taking the Conservative Protestant Thesis Across the Atlantic. A Comparative Analysis of the Relationships Between Violence, Religion and Stimulants Use in Rural Netherlands - Weenink, Don (The British journal of criminology, 2015)
Building upon the Southern culture of violence research tradition, this article inquires the association between rural violence and Conservative Protestantism in the Dutch context. Based on data of 8,106 individuals, it was found that young rural Conservative Protestants living in villages were more likely to report that they had committed violence, as compared to their fellow believers living in urbanized areas. Furthermore, it turned out that the association between alcohol consumption and violence is stronger among this category of religious rural youth. Finally, this study demonstrates that, contrary to the prevailing notion of the idyllic rural, the violence rates between young Dutch rural dwellers and their peers living in the rest of the country are virtually similar.